Women’s land rights as a pathway to poverty reduction: A framework and review of available evidence - Meinzen-Dick, R; Quisumbing, A; Doss, C; Theis, S (Elsevier, 2017)
Land is an important asset for rural households, and having secure land rights is important for poverty reducation. Despit the large body of literature on the relationship between land tenure security, livelihoods, and poverty, most of this literature is based on household-level data and does not consider intrahousehold inequalities in land ownership. However, growing evidence that households do not necessarily pool resources and that women have fewer assets than men warrants attention to the role of women's land rights (WLR) in poverty reduction. This paper adapts to the Gender, Agriculture and Assets Project (GAAP) conceptual framework to identify pathways by which WLR could reduce poverty and increase wellbeing of women and their households in rural areas. It uses a systematic review search methodology to identify papers for inclusion, but adopts a systematic approach to assess the level of agreement and the amount of evidence within this literature. The paper examines the evidence from qualitative as well as quantitative studies on each of these pathways. Owing to the scarcity of experimental studies, the review of empirical work is based mostly on observational studies. We find some evidence on these relationships, but many of the key pathways have not been empirically analyzed. The evidence is strong for relationships between WLR and bargaining power and decision making on consumption, human capital investment, and intergenerational transfers. There is a high agreement, but weaker evidence on the relationship between WLR and natural resource management, government services and institutions, empowerment and domestic violence, resilience and HIV risk, and consumption and food security. There is less agreement and insufficient evidence on the relationship between WLR and other livelihoods, and a higher level of agreement , but limited evidence on associations between WLR and credit, technology adoption, and agricultural productivity. Many gaps in the evidence arise from a failure to account for the complexity of land rights regimes, the measurement of land rights at the household level, the lack of attention paid to gender roles, and the lack of studies from countries outside Africa. The paper concludes that gaps in the evidence should not deter the careful design and implementation of programs and policies to strengthen WLR, given the ongoing land tenure reforms in many countries. If these reforms do not specifically seek to strengthen women's land rights, they are likely to weaken them, with clear negative consequences.